Confini - Boundaries. - Andreoli, Alice; Castro, Jota; Cincinelli, Saretto; Collu, Cristiana; Pinto, Roberto; Senaldi, Marco; Sossai, Maria Rosa; Stalker; Zoletto, Davide (Nuoru : MAN (Museo d'Arte Provincia di Nuoro) Nuoro Silvana Editoriale Cinisello Balsamo (Milano), 2007)
Arena, Francesco ; Bajevic, Maja ; Becheri, Emanuele ; Castro, Jota ; Davids, Yael ; Espaliú, Pepe ; Garaicoa, Carlos ; Hatoum, Mona ; Jaar, Alfredo ; Jetelova, Magdalena ; Kameric, Sejla ; Kostova, Daniela ; Macchi, Jorge ; Maté, Mateo ; Moro, Liliana ; Ingridmwangiroberthutter ; Nacciarriti, Andrea ; Paci, Adrian ; Previdi, Riccardo ; Rakowitz, Michael ; Scurti, Franck ; Spinatsch, Jules ; Stalker ; Taimina, Daina ; Umbaca, Enzo ; Wertheim, Margaret ; Worldmapper Team ; Yass, Catherine ; Burska, Bogna ; Cecchetti, Alex ; de Serio, Gianluca e Massimiliano ; Krippendorff, David ; Linke, Armin ; Malinowski, Jacek ; Woicik, Julita
Confini - Boundaries., Museo d'Arte Provincia di Nuoro, 2006-10-13. 2007-01-07
boek